PENGARUH PEMBIAYAAN PENDIDIKAN DAN SARANA PEMBELAJARAN TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 11 PEKANBARU - Alvionita, Vinni Alvionita Vinni; Armas, Riadi Armas Riadi; ', Sumarno (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research is aimed to know the influence of education funding and means of learning on students learning achievement of class XI IPS in SMA Negeri 11 Pekanbaru. The method used in this research was quantitative descriptive method. The population in this research was all of students in class XI IPS in SMA Negeri 11 Pekanbaru that has 142 peoples. Determination of the total sample used simple random sampling technique, which has 59 students. The data used were the primary data through the spread of questionnaire and the secondary data through the second semester grades of economics in academic year 2013/2014. The data analysis technique used was multiple linear regression. Based on the research results, it could be concluded that the education funding and means of learning influence the students learning achievement both partially or simultaneously. The influence of education funding and means of learning on students learning achievement in class XI IPS SMA Negeri 11 Pekanbaru was 40,2%.bstract: This research is aimed to know the influence of education funding and means of learning on students learning achievement of class XI IPS in SMA Negeri 11 Pekanbaru. The method used in this research was quantitative descriptive method. The population in this research was all of students in class XI IPS in SMA Negeri 11 Pekanbaru that has 142 peoples. Determination of the total sample used simple random sampling technique, which has 59 students. The data used were the primary data through the spread of questionnaire and the secondary data through the second semester grades of economics in academic year 2013/2014. The data analysis technique used was multiple linear regression. Based on the research results, it could be concluded that the education funding and means of learning influence the students learning achievement both partially or simultaneously. The influence of education funding and means of learning on students learning achievement in class XI IPS SMA Negeri 11 Pekanbaru was 40,2%.Keywords: education funding, means of learning, students achievement